POLITICAL PARTIES IN JORDAN FROM 1921 TO 2015, CREATION, EVOLUTION AND CHALLENGES OF A CONTEMPORARY DEMOCRATIC MODEL - Dr. Ali Mohammad Ali AL-Shboul (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The study focuses on the factors behind the weakness of political parties and their performance during the period 1921-2015. To get a holistic view on the factors in question, the research was based on both quantitative and qualitative data. The study then bases its assessment of political parties’ weaknesses on their lack of representation in Jordan’s parliament, their limited influence over public policy, and their unappealing public image (which is manifested by the number of votes the parties receive, the very little affiliation in their ranks, and the general rejection of the parties shown by the censuses conducted by the Centre for Strategic Studies of the University of Jordan). Political parties have never occupied more than 30% of the electoral seats in total (sum of all electoral seats won by political parties) in elections since 1989. Additionally, the vast majority of political parties have only a few hundred members. What elements are driving Jordanian political parties’ weakness, then? The investigation’s goal is to look at the numerous internal and external causes that obstruct political parties’ growth and empowerment, as well as the variables that contribute to their low popularity. This study is supposed to offer light on the solutions available to political parties, as well as the political, institutional, and structural obstacles that must be addressed, in order for political parties to play their political and social roles. East following the democratic initiatives culminating in the Jordanian Spring, and the geopolitical and regional ideologies that resulted from political instability and persecution, the empowerment of political parties arrives at a critical historical juncture. Political parties are unable to form governments under the Constitution, and their power in parliamentary spheres is limited. Despite this, political parties have a small presence in parliaments and a low level of popular support. Despite various reforms to the political system, party system, electoral system, and laws governing public and political freedoms, political parties continue to struggle to win votes in elections and gain the popular support needed to make changes. They claimed that the system would be democratised and that parliamentary governments would be established.